Appendicular endometriosis: Apropos of a case - Ayala, Ayala (2010)
Endometriosis is a condition in which uterine mucosal tissue is located outside the uterus. Endometriosis may be pelvic or extrapelvic, and in this latter case, gastrointestinal tract involvement represents 3-15% of cases, being most frequently located in the rectal-sigmoid region. Appendix involvement in endometriosis is rare, accounting 3-5% of all endometriosis cases. For this reason we present this case of appendicular endometriosis, which was incidentally diagnosed in a patient admitted in the emergency service with a condition resembling acute appendicitis.